Strategi Kepala Sekolah dalam Menguatkan Solidaritas antar Pendidik dalam Perspektif Struktural Fungsional Emile Durkheim: Studi Kasus di SMPIQu Al-Bahjah - Abdalah Fahd Basysyar Al Anwar; Jauharul Ulum (Pusat Riset dan Inovasi Nasional, 2026)
Education is a conscious and planned effort to develop individual potential in order to create qualified human resources. Therefore, to achieve this goal effectively, strong management, good coordination, and solid solidarity among all educational elements are necessary. Solidarity among educators plays an important role in supporting the implementation of educational programs and achieving institutional goals. This study aims to determine the principal's methods and strategies for increasing solidarity among educators in the school environment. This study employed a qualitative research method, with data obtained through observation, in-depth interviews, and documentation related to school activities. The validity of the data was ensured using triangulation techniques to maintain accuracy and credibility. The results show that educator solidarity at SMPIQu Al-Bahjah is implemented through routine deliberations, structured morning briefings, and regular weekly evaluations involving all educators. These activities are consistently carried out as a collective effort to achieve the school’s vision and mission. The implications of this research are expected to provide practical benefits for educational institutions in strengthening educator solidarity. In addition, this research can serve as a reference for other academics in developing and applying Emile Durkheim's structural-functional theory within educational management contexts.